Преобразуйте выражение в многочлен стандартного вида:
а) (2x² - 1)(x + 3);
б) (3y² + 5)(y - 6);
в) (8 - y)(8 + y) - (y + 4);
г) x(x - 3) + (x + 1)(x + 4).

2

Ответы и объяснения

Лучший Ответ!
2014-01-25T17:11:01+04:00
А) (2x² - 1)(x + 3)=2х³ + 6х² - х - 3
б) (3y² + 5)(y - 6)=3у³ - 18у² + 5у - 30
в) (8 - у)(8 + у) - (у + 4)= 64 - у² - у - 4=60 - у² - у
г) х(х - 3) + (х + 1)(х + 4)=х² - 3х + х² + 5х + 4=2х² + 2х + 4
2014-01-25T17:14:31+04:00
а) (2x² - 1)(x + 3) = 2x²(x + 3) -1(x + 3) = 2x³ + 6x² - x - 3
б) (3y² + 5)(y - 6) = 3y²(y - 6)  + 5(y - 6) = 3y³ - 18y² + 5y - 30
в) (8 - y)(8 + y) - (y + 4) = 64 - y² - y - 4
г) x(x - 3) + (x + 1)(x + 4) =
x² - 3x + x² + 5x + 4 = x² + 2x + 4
У меня зависает ответ...............
а) 2х^3 +6x^2-x-3
б) 3y^3-13y^2-30
в) = - y^2 - y +60
= 2x^2+2x+4